Internet Technology Imperatives In Enhancing Customer Relations: An Empirical Study In Klang Valley - Mohd Roslie, Johanniz (2003)
The findings of the study revealed that Internet technology plays a very important role in managing customer relations. Internet technology does not only improve the customer service but more importantantly it can deliver value to the customers that will increase customer retention rate and customer loyalty on the Internet.